Molecular crowding overcomes the destabilizing effects of mutations in a bacterial ribozyme - Lee, Hui-Ting (Nucleic Acids Res, 2015)
The native structure of the Azoarcus group I ribozyme is stabilized by the cooperative formation of tertiary interactions between double helical domains. Thus, even single mutations that break this network of tertiary interactions reduce ribozyme activity in physiological Mg(2+) concentrations. Here, we report that molecular crowding comparable to that in the cell compensates for destabilizing mutations in the Azoarcus ribozyme. Small angle X-ray scattering, native polyacrylamide gel electrophoresis and activity assays were used to compare folding free energies in dilute and crowded solutions containing 18% PEG1000. Crowder molecules allowed the wild-type and mutant ribozymes to fold at similarly low Mg(2+) concentrations and stabilized the active structure of the mutant ribozymes under physiological conditions. This compensation helps explains why ribozyme mutations are often less deleterious in the cell than in the test tube. Nevertheless, crowding did not rescue the high fraction of folded but less active structures formed by double and triple mutants. We conclude that crowding broadens the fitness landscape by stabilizing compact RNA structures without improving the specificity of self-assembly.